Antimicrobial Resistance in Chilean Marine-Farmed Salmon: Improving Food Safety Through One Health - Vasquez-Martinez, y; Cortez-San Martin, M (Elsevier B.V., 2021)
Aquaculture is seen as an essential requirement for improving food security and nutrition. Fish such as salmonids are a primary source of protein and essential nutrients. Aquaculture provide income for communities across the world and have a smaller carbon footprint than terrestrial animal-production systems. However, fish diseases are a constant threat, and the use of antibiotics is a source of concern due to its adverse impacts on the environment and human health. Chilean salmon farming has made several efforts to reduce the use of antibiotics for the eradication of piscirickettsiosis, a disease caused by the gram-negative bacteria Piscirickettsia salmonis. Excessive amounts of antibiotics continue to be used in Chilean aquaculture, playing an important role in the emerging public health crisis of antimicrobial resistance. Without doubt, P. salmonis is becoming increasingly resistant to important frontline antimicrobial classes, with severe implications for the future treatment of infectious human and animal diseases. Antimicrobial-resistant bacteria as well as antibiotic residues from salmon production are spreading in the environment, and thus both salmon food commodities and wild organisms can become a source of resistant bacteria that can be transmitted to humans as foodborne contaminants. This urgent threat needs to be addressed by implementing national strategies in compliance with international standards that include both prudent antimicrobial use in marine salmon farms and the investment towards a One Health approach, which combines human, animal and environmental health. © 2021 The Author(s)